Frequency-to-Time Mapping Technique for Direct Spectral Characterization of Biphoton States From Pulsed Spontaneous Parametric Processes - Khodadad Kashi, Anahita; Sader, Lynn; Haldar, Raktim; Wetzel, Benjamin; Kues, Michael (Frontiers in Photonics, 2022)
The well-established frequency-to-time mapping technique is employed as a novel, convenient and time-efficient method to directly characterize the spectral correlations of biphoton states from a pulsed-excited spontaneous parametric down-conversion processes. We were enabled by this technique to implement for the first time, the spectral Hanbury-Brown and Twiss measurement, revealing directly the single frequency-mode bandwidth of the biphoton state.